2003
DOI: 10.1007/3-540-44860-8_90
|View full text |Cite
|
Sign up to set email alerts
|

Approximation Algorithms to Minimum Vertex Cover Problems on Polygons and Terrains

Abstract: Abstract.We propose an anytime algorithm to compute successively better approximations of the optimum of Minimum Vertex Guard. Though the presentation is focused on polygons, the work may be directly extended to terrains along the lines of [4]. A major idea in our approach is to explore dominance of visibility regions to first detect pieces that are more difficult to guard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Approximate solutions to the Orthogonal Art Gallery problem can be obtained by modeling it as a discrete combinatorial problem, the Minimum Set Cover problem, as shown by Erdem and Sclaroff in [8,9] and by Tomás et al in [23,24]. Both approaches discretize the polygon P in some way and then solve the corresponding optimization problem.…”
Section: The Discretized Orthogonal Art Gallery Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximate solutions to the Orthogonal Art Gallery problem can be obtained by modeling it as a discrete combinatorial problem, the Minimum Set Cover problem, as shown by Erdem and Sclaroff in [8,9] and by Tomás et al in [23,24]. Both approaches discretize the polygon P in some way and then solve the corresponding optimization problem.…”
Section: The Discretized Orthogonal Art Gallery Problemmentioning
confidence: 99%
“…Recently, Erdem and Sclaroff in [8,9] and Tomás et al in [23,24] modeled the problem as a discrete combinatorial problem and then solved the corresponding optimization problem. The results we present here follow this line.…”
Section: Introduction and Related Workmentioning
confidence: 99%
“…In [4] we showed that Π(P ) has at most 1+r +r 2 pieces. Later we noted that this upper bound is not sufficiently tightened.…”
Section: Lower and Upper Bounds On |π(P )|mentioning
confidence: 97%
“…In [4] we showed that |Π(P )| ≤ 1 + r + r 2 , where r is the number of reflex vertices of P . We shall now give sharper bounds both for maxP |Π(P )| and minP |Π(P )|.…”
mentioning
confidence: 99%
“…This has also been a major motivation for us. In particular, we needed a sufficiently large number of varied orthogonal polygons to carry out an experimental evaluation of the algorithm proposed in [13] for solving the Minimum Vertex Guard problem for arbitrary polygons. This problem is that of finding a minimum set G of vertices of the given polygon P such that each point in the interior of P is visible from at least a vertex in G, belonging to the Art Gallery problems [8,16].…”
Section: Introductionmentioning
confidence: 99%